Media Quizizz dan pengaruhnya terhadap hasil belajar sejarah di SMAN 10 Jakarta - Siti Nurfadilah; M Fakhruddin; Nurzengky Ibrahim (Historiography: Journal of Indonesian History and Education, 2022)
This study aims to obtain data on the effect of using Quizizz media on student history learning outcomes at SMA Negeri 10 Jakarta. This research uses experimental research methods. The research design used was True Experimental Design, and the type was Pretest-Posttest Control Group Design. The population in this study were students of class X which consisted of 5 classes, and 2 majors. The research sample is class X IPS 3 as the experimental class, and X MIPA 2 as the control class. Based on statistical calculations, the results obtained 2.896, and the value ofm    1.995 with a 95 percent confidence level (α=0.05). Based on these calculations, it can be concluded that the value of  >  (Ho is rejected and H1 is accepted). With the results of these calculations, it can be said that the use of Quizizz media has an effect on student history learning outcomes at SMA Negeri 10 Jakarta.Penelitian ini bertujuan untuk memperoleh data tentang pengaruh penggunaan media Quizizz terhadap hasil belajar sejarah siswa di SMA Negeri 10 Jakarta. Penelitian ini memakai metode penelitian eksperimen. Desain penelitian yang digunakan adalah True Experimental Design, dan jenisnya adalah Pretest-Posttest Control Group Design. Populasi pada penelitian ini merupakan siswa kelas X yang terdiri dari 5 kelas, dan 2 jurusan. Sampel penelitiannya ialah, kelas X IPS 3 sebagai kelas eksperimen, dan X MIPA 2 sebagai kelas kontrol. Berdasarkan perhitungan statistic, didapatkan hasil  2,896, dan nilai  1,995 dengan tingkat kepercayaan 95 persen. Berdasarkan perhitungan tersebut, dapat disimpulkan bahwa nilai  >    . Dengan hasil perhitungan tersebut dapat dikatakan bahwa, penggunaan media Quizizz berpengaruh terhadap hasil belajar sejarah siswa di SMA Negeri 10 Jakarta.